La restauration du théâtre du château de La Roche-Guyon - Riccardo Giordano (In Situ)
The theatre of the chateau of La Roche-Guyon (Val-d’Oise, France) was inaugurated in 1768 in a hypogeum which already existed at the Enville pavilion. It represents a rare example of a society theatre of the second half of the eighteenth century, complete with boxes and balconies added at the beginning of the nineteenth century and still retaining their original overall disposition. Even more exceptionally, the theatre has also kept a significant part of its original stage machinery and numerous traces of the pieces no longer in place. In order to interpret these, parallels have been made notably with the Queen’s theatre at Versailles. This theatrical ensemble is unique for its precocious date, but it has been in a state of abandonment for decades now and requires a large-scale restoration undertaking, according to studies undertaken since the 1990s. Its preservation is still seriously under threat today and a thorough-going restoration project is currently being defined, under the auspices of the author of this article, the architectural agency Arch-R and a pluri-disciplinary group of restoration experts.